Ochronosis - Srikumar G; Hameedultah A; Arunadevi R; Somasundaram V; Parijatham B O; Ilangovan G (Wolters Kluwer Medknow Publications, 2000)
Ochronosis is a rare disorder, which presents with distinct clinical and biochemical features. A fifty seven year old male presented with fracture femur, osteoarthritis, Oslerâ€s sign, alkaptonuria and cutaneous ochronosis. Though the clinical progression of his alkaptonuria was typical, he presented interesting features including non-uniting fracture and arthritis of big and small joints.